DAMPAK CAPITAL INTENSITY, UKURAN PERUSAHAAN, STRUKTUR MODAL DAN PROFITABILITAS TERHADAP HARGA SAHAM - Susanti, Elly; Azwar, Khairul; Ervina, Nelly (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2025)
The purpose of this research is to determine and analyze the effects of Capital Intensity, Size, Capital Structure, and Profitability on Stock Prices. The object of this research is companies in the automotive and component sub-sector listed on the Indonesia Stock Exchange for the period of 2020 - 2024. The total population consists of 13 companies, and for purposive sampling, the sample in this study is 6 companies. This research uses a quantitative method with panel data regression analysis using Eviews Version 12. The results show that simultaneously, Capital Intensity, Size, Capital Structure, and Profitability have a significant effect on Stock Prices. Meanwhile, partially, Capital Intensity, Size, and Capital Structure have a negative and insignificant effect on stock prices, while Profitability has a positive and insignificant effect on stock prices.